A case Report on the Obstacles in Research Publications in a Rural University, South Africa - B Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Universities are the powerhouse; they generate knowledge through research all over the world. A university without research is a black hole that swallows the taxpayers’ money without contributing much to them. Objective: To highlight the obstacles to carry out research in a rural university of South Africa. Case History: Ms. X was enthusiastic to carry out the research in the university She had so far produced about 100 research articles in peer reviewed journals, despite all odds. She was appreciated nationally and internationally for her work, but the university under study has humiliated and victimized her. This report on Ms. X highlights how this rural university is being disadvantaged by not allowing people to go further. The author will try to present his personal views after informal discussions with various academics and researchers. The highlights of the de-motivating and inhibitory factors are discussed in this manuscript. Conclusion: The main obstacle is lack of transparency and abuse of power at this rural university. The university functions like a secretive society.